A resource management framework for interactive Grids - Kumar, Raj; Talwar, Vanish; Basu, Sujoy (Concurrency and computation, 2004)
Traditional use of Grid computing systems has been for batch jobs in the scientific and academic computing. We envision the next generation Grid computing systems to support graphical interactive sessions. In this paper, we propose a resource management framework for supporting graphical interactive sessions in a Grid computing system. We describe the high‐level architectural resource management framework distributed among the submission node, central scheduler node, and the execution node. We then describe in detail the resource management framework on the execution node. The description of the resource management framework on the scheduler node is kept at a high level in this paper. The framework on execution nodes consists of Resource Management Agents, an Admission Control system and Application Predictor system. The agents on the execution node are Startup Agents, Sensor Agents, Monitoring Agents, Aggregator Agents, Enforcement Agents and Registration Agents. The Session Admission Control system is responsible for determining if a new application session can be admitted to the execution node. An Application Predictor system is responsible for predicting the resource utilization behavior of applications based on data obtained from the Resource Management Agents. The proposed framework allows for implementation of a scalable and extensible middleware for interactive Grid resource management. It supports fine‐grained performance guarantees specified in service level agreements and brings forth some important and novel contributions to enable graphical interactive sessions on Grids. Copyright © 2004 John Wiley & Sons, Ltd.